2003
DOI: 10.1074/jbc.m212211200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Domains within Sox-2 and Sox-11 Involved in Autoinhibition of DNA Binding and Partnership Specificity

Abstract: Sox transcription factors play key regulatory roles throughout development, binding DNA through a consensus (A/T)(A/T)CAA(A/T)G sequence. Although many different Sox proteins bind to this sequence, it has been observed that gene regulatory elements are commonly responsive to only a small subset of the entire family, implying that regulatory mechanisms exist to permit selective DNA binding and/or transactivation by Sox family members. To identify and explore the mechanisms modulating gene activation by Sox prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 45 publications
8
59
0
Order By: Relevance
“…It was shown that both proteins cooperated with Oct-3, while only Sox11 could partner with Brn-2 to activate transcription. 26 Brn-2 is involved in the proliferation of melanoma cells and can, like cyclin D1, be induced by the WNT/Beta-catenin pathway. 27 In the murine system, it has been shown in primary and continuous cell cultures that neuron survival and neurite growth are dependent on Sox11.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that both proteins cooperated with Oct-3, while only Sox11 could partner with Brn-2 to activate transcription. 26 Brn-2 is involved in the proliferation of melanoma cells and can, like cyclin D1, be induced by the WNT/Beta-catenin pathway. 27 In the murine system, it has been shown in primary and continuous cell cultures that neuron survival and neurite growth are dependent on Sox11.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the sequences bound by Sox9 dimers found in the enhancers of genes associated with chondrocyte development, e.g. those for collagens, deviate considerably from the Sox consensus binding (Wiebe et al, 2003), Sox2 (Tomioka et al, 2002), Utf1 (Nishimoto et al, 1999), nestin (Nes) (Tanaka et al, 2004). In contrast to the heterodimers, the Sox9 dimer-binding sequences deviate from the Sox consensus in both sites (Bernard et al, 2003;Bridgewater et al, 2003;Dy et al, 2012;Han and Lefebvre, 2008;Sock et al, 2003).…”
Section: Mechanism Of Action: Sox Proteins Complex With Partner Factorsmentioning
confidence: 99%
“…Sox11 but not Sox2 stimulated the reporter construct in transfection experiments, but only Sox2 was capable of binding to the putative binding site as judged by the EMSA. The authors suggested that there is a domain in the Sox11 protein that has a capability of autoinhibiting its ability to bind DNA in vitro and to activate gene expression in vivo (41). This suggestion may also explain the results we obtained with the Optimedin promoter.…”
Section: Discussionmentioning
confidence: 60%
“…Sox2, Sox11, and Brn1 cDNAs were cloned into the pCMV5 expression vector (41,42) and were kindly provided by Drs. A. Rizzino (University of Nebraska) and D. Robbins (University of Michigan), respectively.…”
Section: Methodsmentioning
confidence: 99%